THE EFFFECT OF PROFITABILITY, LEVERAGE, AND TOTAL ASSET TURNOVER ON FIRM VALUE IN PROPERTY AND REAL ESTATE COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE (IDX) - Imanuel, Demetrio; Susanti, Merry (Graduate Program of Universitas Tarumanagara, 2023)
This research aims to partially test the influence of profitability, leverage, and total asset turnover on company value. This research sample includes 36 property and real estate companies from a total of 85 companies listed on the Indonesia Stock Exchange (BEI) over a three-year period (2020-2022). To test the research hypothesis and achieve the objectives, data was obtained from the BEI database and annual reports published by public property and real estate stock companies in Indonesia. In this context, profitability, as measured by ROA (Return on Assets), and leverage as measured by the equity ratio (DER), as well as turnover of total assets as measured by the total asset turnover ratio, are presented as independent variables. Company value is considered as the dependent variable and is measured using Tobin's Q. The data analysis methods used are descriptive statistics, classical assumption tests, and multiple linear regression analysis using the SPSS (Statistical Package for Social Science) application. This research produces results showing that profitability has a significant positive influence on company value, the leverage variable and total asset turnover have a significant negative influence on company value.